Application of remote sensing and GIS in landslide hazard zonation of Joshimath–Badrinath road corridor, Garhwal Himalaya, India - Shrestha, Ghan Bahadur; ray, P. K. Champati (Journal of Nepal Geological Society, 2007)
In the Himalayan region, slope stability is a major concern for developmental activities. Generally, landslide hazard mapping is carried out to identify relatively stable areas for infrastructural development. In the present study, a statistical technique, called information value method, was used to characterise different geo-environmental parameters. These parameters were then integrated to produce a landslide hazard map in the Garhwal Himalaya, India. The landslide causative factors such as lithology, geomorphology, structure, land use, drainage, and anthropogenic activities were derived from high-resolution satellite images and topographic maps, and the information was integrated in a GIS. The terrain-related factors such as slope and aspect were extracted from a digital terrain model (DTM) derived from the stereo pair data of IRS-P5 Cartosat-1 acquired on 20 November 2005. The map shows that 5%, 51%, 39%, 4%, and 1% of the total study area falls in very low, low, moderate, high, and very high landslide hazard categories, respectively. The Joshimath town as well as A.T. Nala and Marwari villages are some of the most hazardous places in the study area. Similarly, Hanuman Chatti, Benakuh, Dam Site, Lambagar, Binaik Chatti, and Paturi as well as the Govindghat–Ghat and Vishnuprayag–Marwari road corridors fall in high and very high hazard zones.